Seqüências numéricas: um estudo da convergência através de atividades - Nunes, Marly De Nardi Ferraz (2001)
This study discribes research performed with the help of activities that place great emphasis upon the student s actions. Teaching and learning the concepts connected with limits and infinite has proved a hard task, often with unsatisfactory results. In France, Aline Robert has done research with over 1.300 students on the acquisition of the concept of convergence of numerical sequences. The same researcher has concluded that the learning process would be more effective if this concept was taught by means of activities conducted by the students themselves. Inspired by her investigations and also based on Piaget s constructivist theory, we carried out activity work with students from a Faculty of Mathematics, who had still not been introduced to the studies of limits and infinitesimal calculus. The aim of our work was to enable the students to better assimilate concepts related to the convergence of sequences. Based on principles of Didactical Engineering, we prepared and applied a sequence composed of ten activities and one post-test. During these activities we utilized problems to work on the concepts related to numerical sequences and convergence. From analysis of the results we concluded that the procedure described here promoted, in general, an increase in knowledge of the students and, in particular, the acquisition, by most students, of notions related to the concept of convergence of numerical sequences. This experience represented a rupture of our traditional pedagogical practices in favor of a new dynamics, which required of ourselves and of the students a change in posture. Among the conclusions are issues that can be the object of further studies